(untitled) (Al-Academy, 2018)
Represents light a sovereign and importance in cinematography element of what possessed the physical characteristics make it a sharp image detail or opaque, or any other form as he wants the director, Valdu away from the main function, which emerged with the beginnings of cinema, any access to endanger the proper and good, the Alachtgalat dramatic and psychological are deepened performance lighting and functioned in adjacent with the shadows, all the two complement each other, which affects the image details or even the ability to express their personal depths or the social and psychological same place, and this prompted the researcher to determine the search in the following address: (employing lighting to express their personal duplicating film) the researcher has to divide his research, and contains the methodological framework on the research problem formulated The importance and goals aimed at detecting modes of employing lighting to express their personal cinematic duality, and the limits of research and determine the terms. contains the theoretical framework and included a three Anoanat President are: First topic: The lighting concept and engage .....The second topic: the personal in film The third topic: lighting and psychological reaction to the film character The researcher came to indicators of the theoretical framework relied upon as a tool for the analysis of the sample, and then dealt with previous studies that Ti_akl with the subject of his research research measures have contained the research methodology chosen by the researcher to suitability nature of research is descriptive method that involves the analysis, and then the sample that was selected Qsidia, and search tool, and the unit of analysis, and the sincerity of the tool. The fourth quarter included the sample analysis process. findings and conclusions he has reached a researcher to several findings and conclusions, including